Enhancing Economic Participation through Technology: A Modified TAM Study on BIONS at the Investment Gallery - Hutami, Lusia Tria Hatmanti; Pratama, Yhoga Heru; Kusuma, Nala Tri; Ningrum, Nonik Kusuma; Kasidi, Davet (International Journal of Economics Development Research (IJEDR), 2025)
The development of digital technology has brought significant changes in various aspects of life, including in the investment sector. One of the widely used investment applications in Indonesia is BIONS (BNI Sekuritas Innovative Trading System), developed by BNI Sekuritas. This study aims to analyze how Perceived Ease of Use, Perceived Usefulness, and Perceived Enjoyment affect Actual Usage in BIONS applications with Intention to Use as a mediating variable. The model developed in this study uses TAM modification by adding the perceived enjoyment variable. The distribution of this questionnaire is aimed at users who use the BIONS application at the Investment Gallery in Yogyakarta, Indonesia. The researcher used a purposive sampling method with a total of 100 respondents. The results showed that Perceived Ease of Use, Perceived Enjoyment, and Intention to Use had a significant effect on actual usage, while perceived usefulness had not affect significantly.